Data science for connected car insurance : use of trips raw telematics data for knowledge discovery and customers profiling - Spada, Enrico (2021)
Internship Report presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence